Penerapan Metode Gross Up Dalam Penghitungan Pajak Penghasilan Pasal 21 Sebagai Strategi Penghematan Pajak Penghasilan Badan Pada PT XYZ - P. Helen Widjaja; Ade Yono (Jurnal Ekonomi, 2016)
This case study was conducted to see the implementation of tax planning for Income Tax Article 21 using 4 (four) alternatives. Based on the analysis, implementation of the gross-up method will provide greater tax savings compared with other alternatives. Calculation of Income Tax Article 21 using gross-up method can result in increasing employees' gross salary, and also will affect the corporate profit decrease because the expense that can be deducted in the fiscal will be increase, so that the corporate income tax borne by the corporate is going down. On the other hand, the gross-up method is advantageous because the employee will receive larger take-home pay.